The Cost of Reconciliation - Pagura, Federico E. (International review of mission, 1996)
Earlier this year the “confessions” of General Martin Balza and a number of military chiefs shocked the Argentine people and a great part of Latin America. They confessed to their participation in the death squads during the military dictatorship in Argentina and publicly asked for pardon. Bishop Federico E. Pagura of the Methodist Church of Argentina shares his reflections on these revelations.